Alcohol consumption by medical students at a Public University in the State of Pará (Research, Society and Development, 2021)
Objective: available the prevalence of alcohol consumption by students regularly enrolled in the medical school of the Federal University of Pará (UFPA), to outline a socioeconomic profile and the pattern of alcohol consumption among medical students according to the current semester. Methods: a retrospective, descriptive, cross-sectional study with a quantitative approach to assess various aspects of the alcohol and socioeconomic profile of 760 students at the Faculty of Medicine at UFPA. Results: our study revealed a prevalence 71.2% of alcohol consumption, 51.2% of males; the age group between 18 to 25 years old (79.8%); single marital status (95.6%); Catholicism religion (57.7%); the naturalness of metropolitan region of Belém (55.8%); housing with family members (73.3%); family income less than five thousand reais (47.7%); the highest intake of alcoholic beverages by students in the two first years the course and the risk zone I, according to the score obtained in Alcohol Use Disorder Identification Test  (AUDIT). 91% of students said they consume alcohol at a frequency of up to four times a month. Our interviewees did not present any serious problem when we regarded the signs and symptoms of alcohol dependence. Conclusion: the prevalence of alcohol consumption found in this study is worrying and requires attention from the academic community.